2018
DOI: 10.22271/ortho.2018.v4.i3j.99
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic management of post traumatic anterolateral soft tissue ankle impingement

Abstract: Was to evaluate the results of arthroscopic management of anterolateral soft tissue anke impingement (ALSTAI) secondary to ankle inversion injuries. Patients and Methods: We treated 27 cases of ALSTAI by arthroscopic debridement between Jan 2015 and Dec 2016. We excluded cases with associated chondral lesions, mechanical instability. Bony impingement and arthritic ankles. Results: After a mean follow-up period of 15 months (12-240, 24 cases (88%) had complete pain relief while 3 cases (12%) still had pain with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…Similar to our results, the study done in 2018, (8) found that there were no major postoperative complications in any patient.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to our results, the study done in 2018, (8) found that there were no major postoperative complications in any patient.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the current study assessed the studied cases according to site of pathology, showing that majority of cases 40% had Anterolateral pathology, 16% were diffuse ante and post, 12% were Anteromedial and only 32% had diffuse ante pathology. In agreement with our study, it was found that the ankle was approached through standard anteromedial and anterolateral portals, taking care to protect the neurovascular structures (8).…”
Section: Discussionsupporting
confidence: 91%